(untitled) (Journal of Life and Earth Science, 2012)
In five tip sterile lines of hexaploid wheat (Kheri, Mexicani, Pavon-76, Seri-82 and Sonora-64) due to interchange of segments three types of meiotic configuration i.e. ring quadrivalent (oIV), chain quadrivalent (cIV) and trivalent plus univalent (III.I) were found at metaphase I. The observed and expected numbers of meiotic configurations in these translocated lines of wheat were found to following the equations based on normal pairing and non random distribution of chiasmata. Different configurations (oIV, cIV, III.I, oII, cII and I) were analyzed following Jackson and Murray’s (1986) formula. The results revealed that χ2-values for the translocated heterozygotes showed to be fit with the expectation. Data showed good agreement between numbers of expected and observed meiotic configuration and all the lines were in fit to the Ho with p > 0.05. DOI: http://dx.doi.org/10.3329/jles.v6i0.9715 JLES 2011 6: 13-18